Uma ideia a recuperar? A conceção humboldtiana da Universidade e o caso da filosofia - Miguens, Sofia (2020)
In this article I discuss the current state of the Humanities starting from two figures, Wilhelm von Humboldt and Steven Pinker, and from a controversy in which the latter was involved. Throughout the article I will take my own discipline, Philosophy, as a reference.